Adverse Childhood Experience among College Students and Its Relationship with Anxiety and Depression - Anindya Dewi Paramita; Andi Tenri Faradiba (Fakultas Psikologi Universitas Pancasila, 2020)
Adolescents are one group that is prone to experience anxiety and depression. Adverse childhood experiences had the potential to cause anxiety and depression. A quantitative approach using a correlational design was used to explore the association between adverse childhood experiences, anxiety, and depression. There were 62 college students willing to be involved and fill out The Generalized Anxiety Disorder (GAD-7), The Patient Health Questionnaire (PHQ-9), dan Adverse Childhood Experience Questionnaire. Majority of the participants (87,1%) reported experiencing at least one ACE, with the most experienced adversities by the participants were emotional abuse, emotional neglect, and physical abuse. As much as27,4% of the participantsreported experiencing four or more ACEs categories. The experience of emotional abuse was positively and significantly correlated with anxiety and depression. Furthermore, sexual abuse was associated with depression while separation of parents or divorce was related to anxiety. The findings of this study strengthen the link between adverse childhood experiences with mental health in adulthood. Early detection of these adversities might be useful to identify students who are at risk of deterioration in their mental health.